GAMBARAN PERILAKU MAHASISWA FARMASI UNIVERSITAS BINA MANDIRI GORONTALO TERKAIT PEREDARAN PRODUK KOSMETIK ILEGAL DI KOTA GORONTALO - Nurtiara ivanka abas; Ahmad Husain Palli; Yolanda Ngabito (LPPM Universitas Bina Mandiri Gorontalo, 2024)
This study aims to describe the behavior of pharmacy students of Bina Mandiri University Gorontalo towards the use of illegal cosmetics circulating in Gorontalo City. The method in this study is descriptive with a quantitative approach. The population is S1 Pharmacy students of Bina Mandiri University Gorontalo. The research instrument is in the form of a questionnaire distributed through Google form to the study population. The number of samples was 124 people who filled out the google form that was distributed completely. The data were then analyzed univariately with frequency and percentage distributions. The results showed that most pharmacy students of Bina Mandiri University Gorontalo had good knowledge, which was 93 people (75.00%). Meanwhile, students with sufficient knowledge levels were 24 people (19.35%) and less knowledge as many as 7 people (5.65%). In the attitude variable, the number of good categories was 61 people (49.19%). Meanwhile, students with sufficient attitudes were 26 people (20.97%) and less attitudes as many as 37 people (29.84%). In the Good Action category variable, there were 107 people (86.29%). Meanwhile, students with enough actions as many as 10 people (8.06%) and less actions as many as 7 people (5.65%)